2021
DOI: 10.31351/vol30iss2pp41-49
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Toxicity and Health Hazards of the Healthcare Providers at Healthcare Facilities in Sulaimani City, Iraq

Abstract: Objective: The present study aimed to evaluate the occupational health hazards that face health care providers in Sulaimani City. Methods: A cross-sectional study conducted utilizing quantitative data collection methods. It involved 159 respondents including Physicians, Pharmacists, Medical assistants, Laboratory Instructors and Nurses who worked in 8 major health facilities in Sulaimani city, Kurdistan region, Iraq. Results: Nurses were the most susceptible group to sharp related injuries 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…This could increase the number of graduates working in this profession, as well as the wide range of private business options in the city Regarding the career title of HCWs, it was found that the highest percentage (20.8%) of HCWs were medical assists followed by Pharmacists 18.9%. These results are comparable to previous results in the city of Sulaymaniyah by [16]. This is due to the large number of institutes that graduates medical assistants from different department According to the results of this study, a percentage of 46.5% of health workers have 1-5 year of experience.…”
Section: Iiiresults and Discussionsupporting
confidence: 87%
“…This could increase the number of graduates working in this profession, as well as the wide range of private business options in the city Regarding the career title of HCWs, it was found that the highest percentage (20.8%) of HCWs were medical assists followed by Pharmacists 18.9%. These results are comparable to previous results in the city of Sulaymaniyah by [16]. This is due to the large number of institutes that graduates medical assistants from different department According to the results of this study, a percentage of 46.5% of health workers have 1-5 year of experience.…”
Section: Iiiresults and Discussionsupporting
confidence: 87%